Kampanye sebagai Komunikasi Politik - Siti Fatimah (Resolusi: Jurnal Sosial Politik, 2018)
In a state with democratic system, political campaign tremendously becomes essential for introducing a candidate to the society. Political campaign is understood as an organised attempt trying to influence the decision making process in a particular group. Aiming at winning an election, every candidate has to consider some adequate strategies and plans. The strategies and plans are important because they determine the winning of the candidate in the election process. This paper examines the concept of campaign as a part of political communications. By explaining the concept of messages and strategies, this paper concludes that the success of a political campaign requires the planning and formation of a sufficient team to maximize the strategies.